Reactive uveitis, retinal vasculitis and scleritis as ocular end-stage of Acanthamoeba keratitis: a histological study - Shi, Lei; Hager, Tobias; Fries, Fabian Norbert; Daas, Loay; Holbach, Leonard; Hofmann-Rummelt, Carmen; Zemova, Elena; Seitz, Berthold; Szentmary, Nora (International Journal of Ophthalmology, 2019)
We analysed histologically two Acanthamoeba keratitis (AK) eyes with anterior and posterior segment inflammation and blindness. Two enucleated eyes of 2 patients (age 45 and 51y) with AK (PCR of epithelial abrasion positive) were analysed. Histological analysis was performed using hematoxylin-eosin, periodic acid-Schiff and Gomori-methenamine silver staining. We could not observe Acanthamoeba trophozoites or cysts neither in the cornea nor in other ocular tissues. Meanwhile, we found uveitis, retinal vasculitis and scleritis in these eyes, due to the long-standing, recalcitrant AK. So in this stage of AK, systemic immune suppression may be necessary for a longer time period.
CRIS-Team WoS Importer:2019-12-27